2000
DOI: 10.1074/jbc.m001863200
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Activation of Radixin by G13 Protein α Subunit

Abstract: G 13 protein, one of the heterotrimeric guanine nucleotide-binding proteins (G proteins), regulates diverse and complex cellular responses by transducing signals from the cell surface presumably involving more than one pathway. Yeast two-hybrid screening of a mouse brain cDNA library identified radixin, a member of the ERM family of three closely related proteins (ezrin, radixin, and moesin), as a protein that interacted with G␣ 13 . Interaction between radixin and G␣ 13 was confirmed by in vitro binding assay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
95
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(96 citation statements)
references
References 29 publications
1
95
0
Order By: Relevance
“…It has been reported that Ga13 directly interacts with radixin, a member of ERM proteins, and that this interaction results in a conformational activation of radixin. 34 This phenomenon is possibly due to competition between components of the Rho signaling pathway (for example, p115 Rho GEF) and radixin for Ga13 binding, (see Figure 8). Finally, these findings emphasize the role that ADAM10 and the cytoskeleton play in promoting metastatic cancer cell fusion.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that Ga13 directly interacts with radixin, a member of ERM proteins, and that this interaction results in a conformational activation of radixin. 34 This phenomenon is possibly due to competition between components of the Rho signaling pathway (for example, p115 Rho GEF) and radixin for Ga13 binding, (see Figure 8). Finally, these findings emphasize the role that ADAM10 and the cytoskeleton play in promoting metastatic cancer cell fusion.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several proteins that interact with both G␣ 12 and G␣ 13 have been identified, including p115, a Rho guanine nucleotide exchange factor (10), cadherin (11), and radixin (12). Therefore, G␣ 12 and G␣ 13 are thought to transduce mutual downstream signaling through these effectors. In contrast, a variety of GPCRs appear to selectively couple to G␣ 12 or G␣ 13 (13).…”
mentioning
confidence: 99%
“…Therefore, G␣ 12 and G␣ 13 are thought to transduce mutual downstream signaling through these effectors. In contrast, a variety of GPCRs appear to selectively couple to G␣ 12 or G␣ 13 (13). For example, thrombin and lysophosphatidic acid (LPA) have been shown to induce stress fiber formation via G␣ 12 and G␣ 13 , respectively, by using dominant negative mutants of G␣ 12 and G␣ 13 (13).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Several additional pathways might be involved in the a 13 -mediated regulation of cell growth and differentiation since a 13 , as previously demonstrated, is a very powerful transformant, whereas Rho is a weak one (Symons, 1996). Radixin, a member of the ERM family of proteins, and cadherins have also been linked to the transforming ability of a 13 (Vaiskunaite et al, 2000;Meigs et al, 2001Meigs et al, , 2002. Other proteins yet to be identified may also play a role.…”
Section: Discussionmentioning
confidence: 99%